Village Food Barn Transformation Policy Based on Social Capital and Governance for Sustainable Food Security - Ahmad Fajar Fajar Adi Pratama; Noverman Duadji; Novita Tresiana (Universitas Sebelas Maret, 2025)
This study introduces a new policy development analysis framework for transforming village food barns to achieve sustainable food security. The dynamic governance, resulting from public trust and enhanced government capacity, serves as a new adaptive framework—referred to as the agility-genuine model—for addressing climate change and technological readiness. The study aims to formulate a policy scenario for village food barn transformation by adopting a social capital mutualism and governance approach to enhance sustainable food security. A qualitative approach with prospective analysis is employed to explore future scenarios based on several key factors. The study was conducted in Central Lampung Regency, specifically in Pujokerto Village and Rejo Basuki Village. The research successfully formulates a transparent and effective governance strategy model that serves as a foundation for building public trust, optimizing financial resources, ensuring technological readiness, and highlighting the importance of stakeholder collaboration as a crucial element of the sustainable food security system. The findings contribute to strengthening the role of the community and local farmers while also serving as the basis for formulating policy changes in village food barn transformation to achieve national and global food security by 2045.